Investment Contracts - UNCTAD (World Bank, Washington, DC, 2018)
This note provides guidance on the form and content of contracts between investors and governments pertaining to agricultural investments. The best guarantee of positive benefits from foreign investment is a solid foundation of domestic laws that are properly enforced. In many developing countries, however, the necessary domestic laws may not be in place or may not be sufficiently detailed. Even when they are in place, they may not be implemented or enforced. Contracts can help fill the gaps in domestic laws by providing more detailed guidance on what should be contained in the assessments, and using international standards and best practice as the reference points. However, contracts need to be drafted carefully to maximize benefits and reduce risks.